Effect of Sugar Type Variation on Nata de Coco Growth - Attaqy, Fiella; Kurniasih, Surti; Munarti, Munarti (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2023)
The utilization of old coconut still needs to be improved. Old coconut water that is wasted can pollute the soil because of the acetic acid content produced by the fermentation process. Waste of old coconut water can be used as a food product in the form of nata, which has economic value and reduces environmental pollution. Sucrose is a carbon source for making nata de coco because it is an energy source for Acetobacter xylinum bacteria. Varied carbon sources can have different effects on nata de coco growth. The study results are used as learning media in class X high school. This study aimed to determine the effect of coconut sugar, corn sugar, and rock sugar on the quality of nata de coco, the type of sugar that is best for nata de coco growth, and the feasibility of e-booklet learning media. This research used an experimental and one-factor, complete, randomized design. Data analysis used was organoleptic testing juxtaposed with hedonic test, wet weight calculation, thickness, and learning media validation. The results showed that sugar cubes had the highest average value with a wet weight of 292 gr and a thickness of 1.4 cm. The lowest average value is corn sugar, with an average wet weight of 172 grams and a thickness of 0.9 cm. Organoleptic and hedonic testing of corn sugar has the highest value of 14.09. The validated e-booklet has a percentage score of 88.18% with very feasible criteria. Based on the study results, the varied types of carbon sources significantly affect the quality of nata de coco assessed in terms of appearance and organoleptic aspects.